Dependence of central hemodynamic parameters on anthropo-somatotypologic peculiarities in ecto-morphic somatotype adolescence - Sarafinyuk L.A. (Морфологія, 2012)
The article presents the results of construction of the regression models of reographic central hemodynamic parameters on the basis of anthropometric and somatotypological indexes features for practically healthy municipal youth boys and girls ectomorphic somatotype in Ukraine, Podolsk region. For boys with ektomorfs somatotype was found more symptoms according to which the final variant of regressional polynom has a coefficient of determination above 0.50. We have built mathematical models for boys with ektomorfs somatotype for the ten indicators of central hemodynamics, for the girls of the same constitutional type - for five only. Models of reographic central hemodynamic parameters of young men with ectomorphic somatotype often includes suchanthropometric dimensions: thickness of skin and fat folds on the abdomen, the circumference of the chest on inspiration and the face width. For the girls with ectomorphic somatotype in most cases the variability of central hemodynamics parameters determines by skin-fat folds thickness on shin and abdomen.